Kepatuhan Implementasi SOP Sampah Di Kalurahan Tegaltirto Sebagai Dasar Tahap Pemeliharaan Dan Audit: Kepatuhan Implementasi SOP Sampah Di Kalurahan Tegaltirto Sebagai Dasar Tahap Pemeliharaan Dan Audit - Desy Eliana (SIBER PRESS Universitas SIBERMU, 2024)
This study is a continuation of previous research on the development of a Standard Operating Procedure (SOP) for waste management in Kalurahan Tegaltirto. Although the SOP has been established, its implementation still faces challenges such as low public awareness and a lack of supporting infrastructure. This study aims to evaluate the implementation of the SOP as a basis for the maintenance and audit phase to ensure its long-term effectiveness.The research method used is descriptive qualitative, employing observation, interviews, and focus group discussions (FGD). The study sample consists of 40 respondents, including BUMDes managers, waste management officers, village officials, and community representatives. The discussion in this study emphasizes the importance of regular audits, capacity building for officers, and continuous public education to ensure the consistent implementation of the SOP.The conclusion of this study is that the maintenance and auditing of the SOP need to be conducted regularly to ensure more effective and sustainable waste management. It is recommended to improve infrastructure, strengthen regulations, and implement more intensive educational programs to enhance public compliance with the waste management SOP. Keywords: Waste Management, SOP Implementation, Maintenance, Audit.